"Boys and dolls; girls and cars": Children's reactions to incongruent images in a retailer's catalogue. Issue 10 (10th October 2016) - Ulrich, Isabelle; Ezan, Pascale
Abstract : Purpose: French retailer, Système U, has triggered controversial debates among professionals and parents recently, by inserting images revolutionising gender norms in its Christmas toy catalogue. As children's perceptions did not feature in these debates, the purpose of this paper is to explore their reactions to this catalogue, its gender-incongruent images and their associated toys. Design/methodology/approach: An exploratory qualitative study was conducted with 27 children aged five to ten, from middle-upper social class. The methodology combined in one session participant observation, interview with visual stimuli and a collage exercise. First, each child was observed as they browsed freely through the catalogue, commenting it. Second, the interview focussed on four gender-incongruent images inside the catalogue to further explore reactions. Finally, they participated to a collage exercise on a mini-questionnaire, aiming at checking their gender-flexibility. Findings: First, all children tend to focus on their own-gender pages only, as they have an intuitive understanding of the catalogue's gendered structure. Second, incongruent images tend not to be noticed, with an exception being girls aged nine to ten. Third, the children's acceptance of the gender-incongruent images is influenced by the gender-constancy stage, with the rigidity peak about gender norms at five to six; children's own-gender-flexibility, between eight and ten; and the collective nature of the game. Originality/value: This paper reveals children's reactions to a toy catalogue containing gender-incongruent images. It provides new insights into how children notice, understand and appreciate these images and concludes with practical implications for retailers about how to better adapt catalogues.